Revision of the species of Elaphropeza Macquart, 1827 (Diptera: Hybotidae, Tachydromiinae) from Amazon Basin and some remarks about E. ciliatocosta (Bezzi, 1904) - Freitas-Silva, Rafael A. P.; Ale-Rocha, Rosaly (Zootaxa, 2009)
Five species of Elaphropeza Macquart, 1827 from the Amazon Basin region are recognized here and re-described in order to clarify and update previous descriptions, as well as illustrations: E. biseticauda (Smith, 1963), E. flavida (Williston, 1896), E. mazaruni (Smith, 1963) and E. similis (Smith, 1963). Re-description of Elaphropeza monochaeta (Bezzi, 1909) comb. nov. is updated, presenting characters nowadays utilized in taxonomy of this group. The female of E. biseticauda is described and illustrated for the first time and E. bergonzoi Raffone, 2000 syn. nov. is proposed as junior synonym of E. flavida. A key to Elaphropeza species from Amazon Basin is provided. Lectotype designation for E. flavida was made and geographical records of this species and the Australian species E. ciliatocosta (Bezzi, 1904) in the Neotropics are discussed.